IMPLEMENTATION OF ICT INTO THE TEACHING OF MATHEMATICS IN MARITIME UNIVERSITY - Gudyreva, О.М. (Journal of Information Technologies in Education (ITE), 2011)
The main object of informational support of education in maritime university is providing of a new preparation model for future specialists. Mathematics is a fundamental subject in maritime university. ICT affords ground for giving mathematical image in new levels and forms and go along with lecture courses. It helps to pass into dynamic graphical images which demonstrate the behavior not only of the mathematical models of practical assignments but also of the objects and processes in mathematics itself. In maritime university is effectual to have a common educational and scientific field in higher mathematics which is educational course on base of ICT.